In-depth review 2024 (Publications Office of the European Union, 2024)
This in-depth review (IDR) analyses the evolution of the Netherland's vulnerabilities related to high private debt levels and a large current account surplus, which has crossborder relevance, and possibly newly emerging risks. This year's IDR, which follows the 2024 Alert Mechanism Report (AMR) published in November 2023, assesses the persistence or unwinding of the vulnerabilities identified last year, potential emerging risks, and relevant policy progress and policy options that could be considered for the future. Given the size of the Dutch economy and its interlinkages with the other EU Member States, these vulnerabilities have a cross-border relevance.
10.2765/112050
Keywords: Graue Literatur; economic forecasting; macroeconomics; euro area; loan; financial stability; financial supervision; household consumption; gross domestic product; inflation; labour market; EU Member State; Netherlands; report